Datasets for the reporting of neoplasia of the testis: recommendations from the International Collaboration on Cancer Reporting. Issue 1 (18th December 2018) - Berney, Dan M; Comperat, Eva; Feldman, Darren R; Hamilton, Robert J; Idrees, Muhammad T; Samaratunga, Hemamali; Tickoo, Satish K; Yilmaz, Asli; Srigley, John R
Abstract : We here describe the development of an evidence‐based cancer dataset by an International Collaboration on Cancer Reporting expert panel for the reporting of primary testicular neoplasia, and present the 'required' and 'recommended' elements to be included in the pathology report, as well as a commentary. This dataset encompasses the updated 2016 World Health Organisation classification of urological tumours, the results of an International Society of Urological Pathology consultation, and also staging with our preferred method: the American Joint Committee on Cancer version 8. Implementation of this dataset will facilitate consistent and accurate data collection between different cohorts, facilitate research, and hopefully result in improved patient management.